Esensi Moralitas Demokrasi Keadilan: Kriminalisasi Aktivis Dalam Demonstrasi di Indonesia - Rahman, Hafizh Aulia; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
The criminalization of pro-democracy activists in demonstrations in Indonesia is a crucial issue that reveals the paradox between the spirit of democracy and the practice of state power. Normatively, the right to express opinions is guaranteed in Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia, Law No. 39 of 1999 on Human Rights, and Law No. 9 of 1998 on Freedom of Expression in Public, and is even reinforced by international instruments such as the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). However, reality shows that there is a practice of criminalization through the use of vague articles in criminal law directed at pro-democracy activists. This study aims to examine this phenomenon using a normative research approach and critical legal philosophy analysis, specifically Critical Legal Studies (CLS) theory and Michel Foucault's theory of power. The results of the study show that criminalization is not merely a legal deviation, but a strategy of power to discipline society and narrow the public sphere. CLS reveals that the law often functions as an ideological instrument that maintains the dominance of the political elite, while Foucault's analysis shows how the law, apparatus, and discourse of the state work as technologies of power that shape obedience and stigmatize opposition. This phenomenon contradicts the principles of democracy, the rule of law, and substantive justice, which demand equality and respect for citizens' rights. Thus, this study emphasizes that the criminalization of pro-democracy activists must be understood not only as a legal problem, but also as a philosophical and political problem.